Possibility of SADC Monetary Union: Testing for Coordination of Fiscal and Monetary Policies - Mhambi, Balisa; Mishi, Syden (Journal of Reviews on Global Economics, 2019)
There is consensus that fiscal and monetary policies should be coordinated into a broader macroeconomic framework for sustainable monetary union. The Brexit scenario, and the debt problems of some European Union members has vindicated re-consideration of premises on which monetary unions are set-up. Southern African Development Community (SADC) had mooted the idea of a monetary union, despite the Rand Common Currency Area not being successful. However, there has been little literature on coordination of fiscal and monetary policies within and across SADC countries. The aim of this study is to examine whether the key macroeconomic policies are coordinated in order to create a spring-board for a sustainable monetary union. The study employed panel data analysis techniques on 14 SADC countries. The Pooled Mean Group (PGM) method was applied to constrain the long-run coefficients to be identical, but allow the short-run coefficients and error variance to differ across groups. The application of PGM technique allows the study to control for heterogeneity across countries and the time dependence that exist on most macroeconomic series. The empirical results show that there is fiscal and monetary policies coordination amongst some SADC countries. However, cross-country differences on key macroeconomic fundamentals such debts, fiscal balances and money supply may hinder the formation of a monetary union and obstruct the economic survival initiatives for trade amongst member states. The paper concludes monetary union may naturally become necessary to facilitate cooperation and trade amongst countries once there exists shared goals.